Efficient Nondoped Blue Fluorescent Organic Light‐Emitting Diodes (OLEDs) with a High External Quantum Efficiency of 9.4% @ 1000 cd m−2 Based on Phenanthroimidazole−Anthracene Derivative. (17th January 2018) - Tang, Xiangyang; Bai, Qing; Shan, Tong; Li, Jinyu; Gao, Yu; Liu, Futong; Liu, Hui; Peng, Qiming; Yang, Bing; Li, Feng; Lu, Ping
Abstract: Organic light‐emitting diodes (OLEDs) can promise flexible, light weight, energy conservation, and many other advantages for next‐generation display and lighting applications. However, achieving efficient blue electroluminescence still remains a challenge. Though both phosphorescent and thermally activated delayed fluorescence materials can realize high‐efficiency via effective triplet utilization, they need to be doped into appropriate host materials and often suffer from certain degree of efficiency roll‐off. Therefore, developing efficient blue‐emitting materials suitable for nondoped device with little efficiency roll‐off is of great significance in terms of practical applications. Herein, a phenanthroimidazole−anthracene blue‐emitting material is reported that can attain high efficiency at high luminescence in nondoped OLEDs. The maximum external quantum efficiency (EQE) of nondoped device is 9.44% which is acquired at the luminescence of 1000 cd m −2 . The EQE is still as high as 8.09% even the luminescence reaches 10 000 cd m −2 . The maximum luminescence is ≈57 000 cd m −2 . The electroluminescence (EL) spectrum shows an emission peak of 470 nm and the Commission International de L'Eclairage (CIE) coordinates is (0.14, 0.19) at the voltage of 7 V. To the best of the knowledge, this is among the best results of nondoped blue EL devices. Abstract : An efficient blue fluorescent material PIAnCN is reported that exhibits a maximum external quantum efficiency (EQE) of 9.44% in nondoped organic light‐emitting diodes (OLEDs) . The device shows little efficiency roll‐off. The EQE is 9.44% at 1000 cd m −2 and still remains as high as 8.09% at 10 000 cd m −2 . To best knowledge, this is among the best results of nondoped blue fluorescent OLEDs.